PERANAN BANK SUMUT SYARIAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH PADA BANK SUMUT SYARIAH KC MEDAN KATAMSO - Azrin Bahri Harahap; Atika Atika (Akubis : Jurnal Akuntansi dan Bisnis, 2023)
The purpose of this research is to find out the role of the Islamic North Sumatra Bank in the development of micro, small and medium enterprises at the Medan Katamso KC North Sumatra Bank, to find out the factors that hinder the development of Micro, Small and Medium Enterprises (MSMEs). This research includes field research (field research) with qualitative methods that emphasize more on aspects of in-depth understanding of a problem. In essence, field research is research conducted by digging up data sourced from research locations or fields that aim to collect data or information, for example: books, notes, documents, and other references related to MSMEs. The data were obtained from the location of the North Sumatra Sharia Bank, KC Medan Katamso. The results of this study are the role of Islamic banks in optimizing MSMEs, there are three things, namely Availability of MSME financing products in the form of Prosperous North Sumatra, Monitoring financing and business development of customers, and Building MSME capital that will be provided by the Bank, namely in the form of management assistance and business supervision to client. With this research, it is hoped that Bank Sumut Syariah KC Medan Katamso will improve its performance and make employees more comfortable in serving the community, so that people feel comfortable when interacting at Bank Sumut Syarian KC Medan Katamso.